Brand Eouity Of 'Syarah Bakery' In Affecting Customer Purchasing Decisions - Fenti Dwi Sartika; Vethy Octaviani; Anis Endang (SENGKUNI Journal (Social Science and Humanities Studies), 2022)
This study aims to determine Ihe brand eguity 0f Syarah Bakery" in influencing customer purchasing decisions. This study was measured using Ihe Iheory of brand eguity aceonding 0 David A Aaker, 2013: 204 and ihe theory of purchasing decisions hy Kotler Armstrong, 2008. This study sed guantitative Pescareh methods wiih a sample 0f 44 customers. The data analysis technigues were done through simple Jincar. regression, comelation cocficieni, and cocficient 0f determination. The resulis of he study can be coneluded hat Ihere is significant influence. berwen ihe Brand Eguiy 0f Syarah Bakery" on he customers purchasing decision can be proven from ihe brand awareness which is very easy 10 remember and ha its Own eharacteristics. Then it is also proven hy brand association where the product matches Ihe customers taste. The effect is also videnced from Ihe percephon of brand guality where customers feel comfortable and satisfied wilh the product. Until the influence is also explained from brand loyalpy where customers offer ofher consumer products 50 Ihat it affecis Customer purchasing decisions where customers always Pe-purchase he products of Syarah Bakery